Olfactory fMRI Activation Pattern Across Different Concentrations Changes in Alzheimer’s Disease - Zhang, Hui; Ji, Dongxu; Yin, Jianzhong; Wang, Zhiyun; Zhou, Yuying; Ni, Hongyan; Liu, Yawu (Frontiers in Neuroscience, 2019)
The olfactory involvement is an early feature of Alzheimer’s disease (AD). The olfactory functional MRI (fMRI) is an objective method to evaluate the olfactory function, but might be affected by the individual variation and the magnetic susceptibility artifact of basis cranii. To improve the reliability of olfactory fMRI, we explored the response of primary olfactory cortex (POC) across three different concentrations of odors. 44 normal controls, 46 subjects with mild cognitive impairment (MCI), and 44 patients with AD underwent olfactory fMRI using lavender stimuli of three different (0.10%, 0.33%, and 1.00%) concentrations during one fMRI sequence with a 3.0T MRI scanner. The numbers of activated voxels in the POC especially the activation changes during different concentrations were analyzed. The POC activation pattern of controls showed olfactory adaptation at the higher concentration, whereas the AD patients showed not only increased olfactory threshold but also lack of olfactory habituation. Five types of activation patterns across different concentrations were summarized to evaluate the olfactory function. The result showed the activation pattern could effectively found 40/44(90.9%) of the ADs showed impaired habituation, whereas 31/44(70.5%) of the normal controls showed normal olfactory habituation. In MCIs, 29/46(63.0%) of subjects showed impaired habituation. This finding indicates that the POC activation pattern of olfactory fMRI across different concentrations is useful in evaluating the olfactory function, which is important in the detection of early AD among MCI cases.